ARLG in Brighton, UK 2014. Academic libraries: the final frontier. Issue 9 (28th October 2014) - Anderson, Suzanne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to give an overview of the Academic Research Library Group Study Conference hosted by the University of Sussex, in Brighton from the 23rd-25th of June 2014. Design/methodology/approach – A narrative approach was used to describe events. Findings – This was an exciting and action-packed conference that discussed topics surrounding the future of academic libraries. There were several networking opportunities, workshops and an exhibition of sponsors. Originality/value – This report outlines the events of the conference and looks at the themes and issues surrounding the future of research libraries.